Double obstacles increase gait asymmetry during obstacle crossing in people with Parkinson’s disease and healthy older adults: A pilot study - Orcioli-Silva, Diego [UNESP]; Barbieri, Fabio Augusto [UNESP]; dos Santos, Paulo Cezar Rocha [UNESP]; Beretta, Victor Spiandor [UNESP]; Simieli, Lucas [UNESP]; Vitorio, Rodrigo [UNESP]; Lirani-Silva, Ellen [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Springer Nature, 2020)
Gait asymmetry during unobstructed walking in people with Parkinson’s disease (PD) has been well documented. However, under complex situations, such as environments with double obstacles, gait asymmetry remains poorly understood in PD. Therefore, the aim of this study was to analyze inter-limb asymmetry while crossing a single obstacle and double obstacles (with different distances between them) in people with PD and healthy older adults. Nineteen people with PD and 19 healthy older people performed three conditions: (i) walking with one obstacle (Single); (ii) walking with two obstacles with a 50 cm distance between them (Double-50); (iii) walking with two obstacles with a 108 cm distance between them (Double-108). The participants performed the obstacle crossing with both lower limbs. Asymmetry Index was calculated. We found that people with PD presented higher leading and trailing toe clearance asymmetry than healthy older people. In addition, participants increased asymmetry in the Double-50 compared to Single condition. It can be concluded that people with PD show higher asymmetry during obstacle crossing compared to healthy older people, independently of the number of obstacles. In addition, a challenging environment induces asymmetry during obstacle crossing in both people with PD and healthy older people.